Clinical tests accuracy in diagnosing subacromial impingement syndrome: a systematic review - Naqvi, Syed Muhammad Shabbir Ali; Aqsa Sharif; Laiba Javed; Mashal Gul; Hazrat Bilal Malakandi; Aatik Arsh (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the sensitivity and specificity of the clinical diagnostic tests of subacromial impingement syndrome. Method: The systematic review comprised search on PubMed, PEDro, Cochrane Library and Google Scholar databases. For prospective cohort studies published in peer-reviewed English-language journals without any time limit, at least fully describing one clinical test. Only studies with free full text available were included. Data extracted included sensitivity and specificity for each clinical test, and variations were sorted out by the 3 reviewers by discussion. Results: Of the 4137 studies identified, 2951(71.3%) were on PubMed, 119(2.9%) PEDro, 5(0.1%) Cochrane Library and 1062(25.7%) Google Scholar. After screening out all the studies that did not match the detailed inclusion criterion, 3(0.07%) studies were selected for review; 1(33.3%) each done in Spain, Turkey and France. Overall, there were 181 aged 15-82 years; 85(47%) males and 96(53%) females. Supraspinatus palpation test had a sensitivity of 92%, while the modified Neer test had specificity of 95.56% in terms of ruling out subacromial impingement syndrome. Conclusion: Supraspinatus palpation and modified Neer tests were found to be the most effective in the diagnosis of subacromial impingement syndrome. Key Words: Clinical test, Diagnostic accuracy, Sensitivity, Specificity, Subacromial impingement syndrome.